2015
DOI: 10.1007/s11596-015-1442-1
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, pathology, management and prognosis of chronic pancreatitis in Chinese population: A retrospective study

Abstract: The purpose of this study was to investigate the etiology, pathological characteristics, management and prognosis of chronic pancreatitis in the Chinese population. The clinical data of 142 patients with chronic pancreatitis were retrospectively studied. All patients were of Chinese nationality and hospitalized from January 2008 to December 2011. Their ages ranged from 14 to 76 years, with a mean of 43 years. Of 142 patients, there were 72 cases of obstructive chronic pancreatitis (50.70%), 19 cases of alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…(3) The lesion diameter was approximately the same in both diseases and the lesion site which was body and tail of pancreas was common ( figures 2A,2B,2C,2D). (4) The body and tail of pancreas as a location has been showed by many publications [1,13]. (5) The incidence of both diseases increased simultaneously in many countries [29,32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) The lesion diameter was approximately the same in both diseases and the lesion site which was body and tail of pancreas was common ( figures 2A,2B,2C,2D). (4) The body and tail of pancreas as a location has been showed by many publications [1,13]. (5) The incidence of both diseases increased simultaneously in many countries [29,32].…”
Section: Resultsmentioning
confidence: 99%
“…The average diameter of the lesions was 3.6±3.2 in PC group and 3.8±3.3 in CP group as shown in table 1 and the most common lesions site was head of pancreas in both diseases. [1,15] Epidemiological report showed a parallel increase in both diseases in many countries. Niderau et al [16] found the prevalence of pancreatic cancer with CP to be 3.5 % and Lowenfel et al [17] showed a prevalence of 2.9%.…”
Section: Demographic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Aber es bedarf höchstwahrscheinlich noch weiterer Faktoren, um die CP auszulösen (siehe 9.2.2.). Die Häufigkeit der autoimmunen Pankreatitis in CP-Kohorten liegt zwischen 4-9,8 %, ist aber in Asien viel häufiger als in Europa [355,356]. Eine Hypertriglyceridämie (> 1000 mg/dl) kann eine rezidivierende akute Pankreatitis bedingen, welche ohne Behandlung der Ursache möglicherweise im Verlauf Kriterien einer Diagnosestellung der CP erfüllt.…”
Section: Kommentarunclassified